2012
DOI: 10.7710/2162-3309.1053
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Campus Culture: Collaborations and Collisions

Abstract: From the 2007 implementation of Illinois Wesleyan University’s institutional repository (IR), an archivist and special collections librarian and a scholarly communications librarian have worked on its development and expansion from each position’s unique perspective. They have found themselves united on some fronts, but divided at times on big picture questions such as the definition of campus culture and the extent to which the IR should contain products of that culture, how best to describe and structure col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The records and archives department was established in 1990 as part of the library to preserve institutional memory (Sulej 2009). Archives repository preserve research activities and creative efforts of students' records of the university (Miner & Kahl 2012). The university archivist was appointed in 2015.…”
Section: The Historical Background Of the University Of Vendamentioning
confidence: 99%
See 1 more Smart Citation
“…The records and archives department was established in 1990 as part of the library to preserve institutional memory (Sulej 2009). Archives repository preserve research activities and creative efforts of students' records of the university (Miner & Kahl 2012). The university archivist was appointed in 2015.…”
Section: The Historical Background Of the University Of Vendamentioning
confidence: 99%
“…Management of student affairs records is an integral part of comprehensive archives and records management programme (Popoola 2007). The study conducted by Miner and Kahl (2012) indicated that most of the African universities lack an integral strategy to manage student affairs records throughout the records' lifecycle. The interconnectedness of divisions is an integral part of managing university records that raises issues of archiving student affairs records.…”
Section: Name Of Universities Year Of Archives Establishmentmentioning
confidence: 99%
“…Beyond this background of goals and university objectives, the university archives pursue the project amid an increasing attention to collaborate with the Student Affairs Department (SAD) to ensure the collection of the student affairs records (SARs). Archives are seen as a means of documenting the outcomes of research and creative efforts of students, staff and faculty and of addressing the need for storing and accessing records of the university (Miner and Kahl, 2012). The Records and Archives Department aims to improve access to archival collections.…”
Section: Introduction and The Historical Background Of The University Of Mpumalangamentioning
confidence: 99%
“…The study conducted by Wagner and Smith (2012) during their pilot project on records management found that to improve records management guidance was to recognise the need to make information easily accessible through online platforms; however, the study never indicated at what point records will be made accessible to the users. The establishment of archives provides access to the university records as well as evidence of student life culture (Miner and Kahl, 2012).…”
Section: Introduction and The Historical Background Of The University Of Mpumalangamentioning
confidence: 99%